Aqueous zinc ion battery positive electrode material and preparation method and application thereof
Through one-step calcination method, zinc ions are embedded in the positive electrode material of the aqueous zinc ion battery to form a high-performance zinc ion doped VO2 material, solving the problems of unstable structure of the existing material and complex preparation process, and achieving high capacity, low cost and good cycling performance.
Patent Information
- Application Number
- CN202411713122.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-25
AI Technical Summary
The structure of the existing water-based zinc ion battery positive electrode material is unstable during the circulation process, resulting in capacity attenuation. The traditional high-temperature and high-pressure hydrothermal or solvothermal reaction methods are low in safety, high in cost, long reaction time, and cumbersome steps, which are not suitable for industrial production.
The one-step calcination method is used to mix and grind ammonium metavanadate and zinc sulfate evenly, calcined under a protective atmosphere, and intercalated between zinc ions and vanadium oxide layers to form a high-performance zinc ion doped VO2 material.
It improves the structural stability and specific capacity of the material, simplifies the preparation process, reduces cost and reaction time, enhances safety, is suitable for industrial mass production, and significantly improves the circulation performance and energy density of water-based zinc ion batteries.
Smart Images

Figure CN119683680A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aqueous zinc ion battery materials, and particularly relates to a low-cost and high-capacity aqueous zinc ion battery positive electrode material that is simple and convenient to prepare, and further discloses a preparation method and application thereof. Background Art
[0002] Since solar energy, geothermal energy, wind energy and other energy sources are greatly affected by geography and environment, it is imperative to develop energy storage systems with high energy density, safety and reliability. In today's energy storage systems, lithium-ion batteries with advantages such as high energy density and wide chemical window have achieved great success in commercialization. However, the scarcity of lithium resources, the use of toxic and flammable organic electrolytes, high prices, and frequent safety issues have limited its further development.
[0003] In contrast, aqueous zinc-ion batteries have a higher theoretical capacity (820 mAh g) due to their abundant zinc resources and the characteristics of multivalent ions, i.e., multi-electron transfer. -1 ) and lower redox potential (-0.76V vs standard hydrogen electrode), the use of low-cost aqueous electrolytes, safety, environmental protection, simple operation and many other advantages have made it a new powerful energy storage solution.
[0004] Among them, suitable positive electrode materials are an important component of aqueous zinc-ion batteries. In recent years, the materials widely used in aqueous zinc-ion positive electrodes mainly include three categories: Prussian blue analogues, manganese-based oxides, and vanadium-based oxides. Among them, Prussian blue analogues have a lower specific capacity (<70mAh g -1 ), resulting in a low energy density. At the same time, unstable phase changes during the cycle will lead to capacity decay, making it unable to meet commercial needs. The disproportionation reaction of manganese-based compounds during the cycle causes structural transformation and manganese dissolution, resulting in structural collapse of electrode materials, rapid capacity decay, and poor cycle reversibility, which also limits the further application of manganese-based oxides in zinc-ion batteries.
[0005] Most vanadium oxides have rich layered or tunnel three-dimensional structures with large interlayer spacing. The energy storage mechanism of vanadium-based oxides is the intercalation mechanism of zinc ions embedding and de-embedding between layers. Vanadium-based compounds maintain the stability of the host structure to a great extent during the process of cation entry and exit, showing good electrochemical properties, multi-electron redox reactions, multiple oxidation states (i.e. V 2+ 、V 3+ 、V 4+ and V 5+ ) and higher reversible capacity (>300mAh g -1 ), and other characteristics, and is considered to be one of the most promising ZIBs cathode materials.
[0006] Vanadium-based oxides have been widely used in aqueous zinc-ion batteries. In order to further improve the specific capacity of batteries, doped vanadium oxides have been widely studied, such as cation doping, sulfur doping, etc. However, the most commonly used synthesis methods of doped vanadium oxides are high-temperature and high-pressure hydrothermal or solvent thermal reactions, or two-step hydrothermal reactions followed by calcination. The conditions are relatively harsh, the safety is relatively low, the reaction time is relatively long (usually >24h), and because of the liquid phase reaction, subsequent filtration operations are required, the steps are relatively cumbersome, and it is not conducive to industrial scale-up production. In previous reports, patent application CN115417455 A calcined ammonium metavanadate at 300°C for 2h in an argon atmosphere to obtain NH4 + Doped V2O5 materials, NH4 + It enters the interlayer of V2O5, plays the role of expanding the interlayer distance, and then promotes the insertion and extraction of zinc ions during the charge and discharge process, which has practical significance in improving the capacity and rate performance of zinc ion batteries. Patent application CN 115483392A first reacts V2O5 with oxalic acid in an aqueous solution, dries and grinds the obtained product, and then calcines it with sulfur powder in an inert atmosphere to obtain sulfur-doped VO2 / V6O with a heterogeneous structure. 13 , but this method uses a two-step reaction of liquid phase method and calcination method, which is relatively cumbersome, and the raw material uses expensive V2O5, which is not conducive to industrial scale-up production. Based on this, the present invention uses ammonium metavanadate as the vanadium source, zinc sulfate provides zinc ions, and one-step calcination to synthesize high-performance zinc ion-doped VO2 materials. Compared with traditional hydrothermal reactions, it has significant advantages in industrial mass production, reaction time, cost and safety. The introduction of zinc ions acts as a pillar between the vanadium oxide layers, improves the structural stability and specific capacity of the material, and provides an effective path for synthesizing low-cost and high-capacity aqueous zinc ion battery electrode materials. Summary of the invention
[0007] Based on the technical problems existing in the prior art, one of the purposes of the present invention is to provide a method for preparing a high-capacity and low-cost aqueous zinc ion positive electrode material, in which ammonium metavanadate and zinc sulfate are mixed and ground evenly, and calcined under a protective atmosphere to obtain a zinc ion-doped VO2 material. The method uses a one-step calcination method to embed zinc ions into the vanadium oxide interlayer, protect the stability of the layered structure during the cycle, and improve the specific capacity and cycle stability of the material. The zinc ion-doped VO2 material obtained by the method described in the present invention is used as an aqueous zinc ion battery positive electrode, showing excellent rate performance and good cycle capacity.
[0008] In order to achieve the above object, the technical solution of the invention is as follows:
[0009] S1. Mix and grind ammonium metavanadate and zinc sulfate or its hydrate to obtain a reaction precursor;
[0010] S2. calcining the reaction precursor obtained in S1 under a protective atmosphere.
[0011] Furthermore, in step S1, the molar ratio of ammonium metavanadate to zinc sulfate heptahydrate is 1:1 to 16:1, and the molar ratio is preferably 8:1.
[0012] Furthermore, in step S2, the calcination temperature is 400-500°C, and the calcination temperature is preferably 400°C.
[0013] Furthermore, in step S2, the calcination time is 3 h to 5 h, preferably 4-5 h, and the calcination time is more preferably 4 h.
[0014] The present invention adopts a one-step calcination method to carry out the reaction, adopts a solid phase method, does not require additional filtering operations, has high safety, saves costs, has high yield, and provides an effective way to achieve industrialized mass production.
[0015] A second object of the present invention is to provide a zinc ion-doped VO2 material, which is prepared by the above-mentioned preparation method.
[0016] The third object of the present invention is to provide an aqueous zinc ion battery positive electrode material, which is made of the zinc ion-doped VO2 material.
[0017] A fourth object of the present invention is to provide an application of the aqueous zinc ion battery positive electrode material in the preparation of an aqueous zinc ion battery positive electrode.
[0018] A fifth object of the present invention is to provide a positive electrode plate for an aqueous zinc ion battery, which comprises the above-mentioned positive electrode material for an aqueous zinc ion battery.
[0019] A sixth object of the present invention is to provide an aqueous zinc ion battery, which comprises the above-mentioned electrode.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The one-step calcination method of the present invention is simple to prepare high-capacity and low-cost aqueous zinc ion positive electrode zinc ion doped VO2 material. Ammonium metavanadate and zinc sulfate heptahydrate are used as basic raw materials, and after grinding and mixing, they are calcined in a nitrogen atmosphere. Compared with hydrothermal reaction, it has higher safety, lower production cost, and is easy to industrialize and scale up to achieve mass production.
[0022] The present invention adopts a one-step calcination method to embed zinc ions into the interlayer of vanadium oxide, thereby protecting the stability of the layered structure during the cycle process. The zinc ion-doped VO2 material of the present invention is used in aqueous zinc ion batteries, which have high specific capacity and energy density, excellent cycle performance, and good commercial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A flow chart of the preparation of vanadium oxide prepared by the present invention;
[0024] Figure 2 It is the XRD pattern of the product obtained by the reaction in Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 1;
[0025] Figure 3 The product obtained by the reaction in Example 1, Example 2, Example 3, Example 4, and Example 5 was 5.0Ag -1 Charge and discharge cycle diagram under current density;
[0026] Figure 4 is a SEM image of the product obtained by the reaction in Example 3;
[0027] Figure 5 is a SEM image of the product obtained by the reaction in Example 4;
[0028] Figure 6 a is the full XPS spectrum of the products obtained in the reactions of Example 4 and Comparative Example 1; Figure 6 b is the V 2p high-resolution XPS spectrum of the products obtained in the reactions of Example 4 and Comparative Example 1; Figure 6 c is the O1s high-resolution XPS spectrum of the products obtained in the reactions of Example 4 and Comparative Example 1; Figure 6 d is the Zn 2p high-resolution XPS spectrum of the product obtained in the reaction of Example 4;
[0029] Figure 7 is a SEM image of the product obtained by the reaction in Example 5;
[0030] Figure 8 is the XRD pattern of the product obtained in the reaction of Example 6 and Example 7;
[0031] Fig. 9 is a SEM image of the product obtained by the reaction in Example 6;
[0032] Fig.10 The product obtained by the reaction in Example 6 and Example 7 was 5.0Ag -1 Charge and discharge cycle diagram under current density;
[0033] Fig.11 is a SEM image of the product obtained by the reaction in Example 7;
[0034] Fig.12 is the XRD pattern of the product obtained in the reaction of Example 8 and Example 9;
[0035] Fig.13is a SEM image of the product obtained by the reaction in Example 8;
[0036] Fig.14 The product obtained by the reaction in Example 8 and Example 9 was 5.0Ag -1 Charge and discharge cycle diagram under current density;
[0037] Fig.15 is a SEM image of the product obtained by the reaction in Example 9;
[0038] Fig.16 The product obtained by the reaction in Example 4 and Comparative Example 1 was 5.0A g -1 Schematic diagram of charge and discharge cycle under current density. DETAILED DESCRIPTION
[0039] In order to make the content of the present invention easier to understand, the specific implementation details are fully described in the following description, and detailed implementation methods and operation processes are given. It should be noted that ordinary technicians in this field can make similar improvements without departing from the principles of the present invention. These improvements should be regarded as the protection scope of the present invention. Therefore, the present invention is not limited to the specific implementations disclosed below:
[0040] Example 1
[0041] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0042] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.575 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (2 mmol) (molar ratio of 1:1), mix and grind evenly to obtain a reaction precursor.
[0043] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 2 , electrochemical performance see Figure 3 .
[0044] Example 2
[0045] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0046] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.288 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (1 mmol) (molar ratio of 2:1), mix and grind evenly to obtain a reaction precursor.
[0047] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 2 , electrochemical performance see Figure 3 .
[0048] Example 3
[0049] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0050] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.1435 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (0.5 mmol) (molar ratio of 4:1), mix and grind evenly to obtain a reaction precursor.
[0051] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 2 , SEM see Figure 4 , electrochemical performance see Figure 3 .
[0052] Example 4
[0053] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0054] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.072 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (0.25 mmol) (molar ratio of 8:1), mix and grind evenly to obtain a reaction precursor.
[0055] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 2 , SEM see Figure 5 The full XPS spectrum and detailed spectra of V 2p, O1s, and Zn 2p are shown in Figure 6 , electrochemical performance see Figure 3 .
[0056] Example 5
[0057] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0058] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.036 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (0.125 mmol) (molar ratio of 16:1), mix and grind evenly to obtain a reaction precursor.
[0059] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 2 , SEM see Figure 7 , electrochemical performance see Figure 3 .
[0060] Example 6
[0061] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0062] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.072 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (0.25 mmol) (molar ratio of 8:1), mix and grind evenly to obtain a reaction precursor.
[0063] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 300°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 8 , SEM see Fig. 9 , electrochemical performance see Fig.10 .
[0064] Example 7
[0065] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0066] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.072 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (0.25 mmol) (molar ratio of 8:1), mix and grind evenly to obtain a reaction precursor.
[0067] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 500°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 8 , SEM see Fig.11 , electrochemical performance see Fig.10 .
[0068] Example 8
[0069] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0070] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.072 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (0.25 mmol) (molar ratio of 8:1), mix and grind evenly to obtain a reaction precursor.
[0071] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 3h at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Fig.12 , SEM see Fig.13 , electrochemical performance see Fig.14 .
[0072] Example 9
[0073] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0074] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and 0.072 g of zinc sulfate heptahydrate (ZnSO4·7H2O) (0.25 mmol) (molar ratio of 8:1), mix and grind evenly to obtain a reaction precursor.
[0075] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 5 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Fig.12 , SEM see Fig.15 , electrochemical performance see Fig.14 .
[0076] Comparative Example 1
[0077] The one-step calcination method is used to prepare the vanadium oxide positive electrode material. The process of the preparation method is as follows: Figure 1 As shown, the following steps are included:
[0078] S1. Weigh 0.234 g of ammonium metavanadate (NH4VO3) (2 mmol) and grind it evenly to obtain a reaction precursor.
[0079] S2. The reaction precursor obtained in S1 was placed in a nitrogen atmosphere and calcined at 400°C for 4 hours at a heating rate of 5°C / min. The vanadium oxide positive electrode material was obtained. The XRD of the vanadium oxide positive electrode material prepared in this example is shown in Figure 2 , V 2p and O1s XPS fine spectra are shown in Figure 6 , electrochemical performance see Fig.16 .
[0080] The reaction conditions and electrochemical properties of the vanadium oxide positive electrode materials prepared in all the above examples and comparative examples are shown in Table 1.
[0081] Table 1
[0082]
[0083]
[0084] Performance Testing
[0085] Weigh the binder polyvinylidene fluoride (PVDF) and nitrogen methyl pyrrolidone (NMP) at a mass ratio of 20:1, stir at room temperature for 24 hours until PVDF is completely dissolved in NMP, and obtain a uniform solution with a mass fraction of 5% PVDF. Weigh the positive electrode material and the conductive agent acetylene black in the embodiment at a mass ratio of 7:2, place them in an agate mortar and grind them thoroughly until they are evenly mixed, then add a suitable PVDF uniform solution with a mass fraction of 5% according to the mass ratio of the positive electrode composite material, the conductive agent acetylene black, and the binder PVDF of 7:2:1, then add 0.5mL NMP and stir thoroughly, then evenly coat it on a stainless steel foil, dry it in a vacuum oven at 50°C for 5 hours, and obtain the required electrode sheet as the positive electrode, assemble a CR2025 button battery, 3mol / L Zn(CF3SO3)2 as the electrolyte, medium-speed qualitative filter paper as the battery separator, and commercial zinc sheet as the negative electrode, and assemble it into a button battery in air. At room temperature (25°C), the charge and discharge test was performed using the Blue Electric test system: constant current charge and discharge mode was used at 0.2V~1.6V (vs. Zn 2+ / Zn) voltage range for cycle performance test, performance see Figure 3 , Fig.10 , Fig.14 , Fig.16 .
[0086] Results Analysis
[0087] Depend on Figure 2It can be seen that the four main characteristic peaks at 15.4°, 25.6°, 30.48°, and 49.7° can all match VO2 (PDF#31-1438). When the molar ratio of ammonium metavanadate to zinc sulfate heptahydrate is 1:1 and 2:1, that is, when the zinc content is high, in addition to the main peak of VO2 (PDF#31-1438), there are also significant miscellaneous peaks at 18.89°, 20.94°, 21.59°, 26.48°, and 36.82°, indicating that when a large amount of zinc is added, impurities may be generated, resulting in an impure product. As the amount of zinc is reduced to 8:1 and 16:1, the above-mentioned miscellaneous peaks gradually disappear. When all is ammonium metavanadate, that is, no zinc source is added, the diffraction peaks of the calcined product are basically consistent with the XRD diffraction peaks of the calcined product when the molar ratio of ammonium metavanadate to zinc sulfate heptahydrate is 8:1 and 16:1, that is, the products are all VO2. This shows that when the amount of zinc source added is small, the crystal form basically remains unchanged. Figure 8 It can be seen that when the calcination temperature is 300°C, the
[0088] The characteristic diffraction peaks of V2O5 (PDF#53-0583) appeared at 400°C and 500°C. As the temperature increased to 400°C and 500°C, the characteristic diffraction peaks of V2O5 gradually disappeared, and were replaced by the characteristic diffraction peaks of VO2 (PDF#31-1438) at 15.46°, 25.69°, 30.77°, 33.9°, 45.8°, and 49.7°. This indicates that when the calcination temperature is low, the product crystal form is V2O5, and when the calcination temperature is high, the product crystal form is VO2, indicating that the reaction temperature has a greater influence on the product crystal form. Fig.12 It can be seen that when the calcination time is 3h, 4h and 5h, the XRD of the obtained calcined product shows relatively consistent diffraction peaks, which can all correspond to the characteristic diffraction peaks of VO2 (PDF#31-1438), indicating that the reaction time has little effect on the crystal form. When the reaction time is 4h, the diffraction peak at 25.64° can correspond to the (110) crystal plane of VO2 (PDF#31-1438), which is sharper and has the largest diffraction peak intensity, indicating that its crystallinity is the highest. In each embodiment and comparative example, no obvious ZnO characteristic diffraction peak appears in the XRD spectrum of the zinc-containing calcined product, indicating that there is no ZnO phase in the product. In Example 4, the zinc element in the product may enter the VO2 lattice.
[0089] Depend on Figure 4 , Figure 5 and Figure 7It can be seen that when ammonium metavanadate and zinc sulfate heptahydrate are used as raw materials and calcined at 400°C in a nitrogen atmosphere for 4 hours, the products are all irregularly shaped lumps with uneven and rough surfaces. When the ratio of ammonium metavanadate to zinc sulfate heptahydrate is 4:1, the size of the lumps is larger. When the ratio of ammonium metavanadate to zinc sulfate heptahydrate is 8:1, the size of the lumps is relatively uniform, about 5 microns. When the ratio of ammonium metavanadate to zinc sulfate heptahydrate is 16:1, it can be observed that the size of the lumps is extremely uneven. When the calcination time is maintained for 4 hours, the ratio of ammonium metavanadate to zinc sulfate heptahydrate is 8:1, and the calcination temperature is 300°C, the morphology of the material can be observed ( Fig. 9 ) is still an irregular block, but the surface of the block is relatively smooth and dense. When the calcination time is kept for 4 hours, the ratio of ammonium metavanadate to zinc sulfate heptahydrate is 8:1, and the calcination temperature is 500℃, the morphology of the material can be observed ( Fig.11 ) has undergone a significant change, with more flakes and a correspondingly smaller size. When the calcination temperature is kept at 400°C, the ratio of ammonium metavanadate to zinc sulfate heptahydrate is 8:1, and the calcination time is changed to 3h( Fig.13 ) and 5h( Fig.15 ), as the calcination time increases, the size of the block increases. Changes in the ratio of ammonium metavanadate to zinc sulfate heptahydrate, reaction temperature, and reaction time have a certain influence on the product morphology and particle size. The calcination temperature has a greater influence on the morphology. The product size is large and the surface is smooth and dense when the calcination temperature is low. The product surface is rough and the size is small when the calcination temperature is high. As the proportion of ammonium metavanadate in the precursor increases, the product size decreases. The calcination time has little effect on the material morphology, but the product particle size increases as the calcination time increases.
[0090] Figure 6 a is the XPS full spectrum of the product obtained by the reaction in Example 4 and Comparative Example 1. In the XPS full spectrum of Example 4, 517.49eV, 530.52eV, and 1022.21eV correspond to V 2p, O 1s, and Zn 2p, respectively, indicating that the vanadium oxide material is composed of V, O, and Zn elements, wherein the V element accounts for 31.75%, the O element accounts for 64.33%, and the Zn element accounts for 3.92%, and the molar ratio of V, O, and Zn in the product is 8.10:16.41:1. In the XPS full spectrum of Comparative Example 1, 517eV and 530eV correspond to V 2p and O1s, respectively, indicating that the vanadium oxide material is composed of V and O elements, wherein the V element accounts for 33.78%, the O element accounts for 66.22%, and the molar ratio of V and O in the product is 1:1.96. Figure 6 b is a comparison of the V 2p high-resolution XPS spectra of the products obtained in Example 4 and Comparative Example 1, wherein the V 2p fine spectrum of Example 4 shows two pairs of V at binding energies of 517.2 eV and 524.7 eV, respectively.4+ The peaks of V 3+ The peak value of V 4+ The proportion is 58.14%, V 3+ The proportion is 41.86%. Similarly, in the V 2p fine spectrum of Comparative Example 1, two pairs of V 4+ The peaks of V 3+ The peak value of V 4+ The proportion is 65.27%, V 3+ The results show that the product V obtained by calcination in Example 4 after adding the zinc source is 34.73% compared with the comparative example 1 when all the zinc source is ammonium metavanadate, that is, no zinc source is added. 4+ The ratio of V 3+ The XRD patterns of the samples in Example 4 and Comparative Example 1 show no diffraction peaks of V2O3 crystals, indicating that the non-stoichiometric O and Zn atoms in the VO2 crystals cause defects in the crystals, which in turn causes the valence of some V to change from V 4+ Reduce to V 3+ The XRD patterns of the samples in Example 4 and Comparative Example 1 show no diffraction peaks of zinc compound crystals, which further indicates that zinc ions have been completely embedded in the VO2 crystals. 3 / 2 The peak of V 3+ The peak of V 4+ The peak of Zn 2+ It has a strong electronic interaction with VO2, resulting in a positive shift in binding energy. Figure 6 c is a comparison of the O1s high-resolution XPS spectra of the products obtained in Example 4 and Comparative Example 1. In the O1s fine spectrum of Example 4, the peak at 529.78 eV binding energy corresponds to VO, and the peak at 531.58 eV binding energy corresponds to oxygen defects, of which oxygen defects account for 48.95% and VO bonds account for 51.05%. Similarly, in the O1s fine spectrum of Comparative Example 1, the peak at 529.6 eV binding energy corresponds to VO, and the peak at 531.4 eV binding energy corresponds to oxygen defects, of which oxygen defects account for 21.83% and VO bonds account for 78.17%. This further shows that the presence of oxygen defects may be the cause of some V in the VO2 product obtained by calcination. 4+ Transformed to V 3+The main reason is that the proportion of oxygen defects in the product obtained by calcination in Example 4 after adding the zinc source is higher than that in Comparative Example 1 when all the zinc sources are ammonium metavanadate, that is, no zinc source is added. This further illustrates that the zinc ions are embedded in the VO2 interlayer, causing the electron cloud distribution around some oxygen atoms originally bound to vanadium to change, forming oxygen defects, and more oxygen defects can further reduce the valence of the vanadium element. This is also consistent with the previous analysis and speculation that the product obtained by calcining Example 4 after adding the zinc source has V 3+ is consistent with a higher proportion. Figure 6 In the Zn 2p fine spectrum shown in d, the peaks at 1045.7 eV and 1022.6 eV correspond to the Zn 2p 1 / 2 and Zn 2p 3 / 2 , indicating that the prepared VO2 material contains divalent zinc element.
[0091] As shown in Table 1, the molar ratios of the products V and Zn obtained in Example 1, Example 2, Example 3, Example 4 and Example 5 are 1.05, 1.98, 3.91, 8.11 and 16.12, respectively. The molar ratios of the products V and Zn obtained in Example 6 (300°C), Example 4 (400°C) and Example 7 (500°C) are 7.96, 8.11 and 8.14, respectively. It can be seen that with the increase of calcination temperature, the molar ratio of the obtained products V and Zn gradually increases. The molar ratios of the products V and Zn obtained in Example 8 (3h), Example 4 (4h) and Example 9 (5h) are 8.05, 8.11 and 8.17, respectively. It can be seen that with the increase of calcination time, the molar ratio of the obtained products V and Zn gradually increases. The main reason for the increase of the molar ratio of V and Zn due to the increase of calcination temperature and calcination time may be caused by the volatilization of zinc.
[0092] Depend on Figure 3 As shown in Table 1, in Example 1, Example 2, Example 3, Example 4 and Example 5, the -1 The capacity after 1000 cycles is 64.1 mAh g -1 、102.7mAh g -1 , 114.4mAh g -1 、188.3mAh g -1 and 107.5mAhg -1 It can be seen that when the amount of zinc source added is too much, the battery capacity is reduced. This may be because the impurities generated make the product impure, and when the amount of zinc source added is small, the effect of improving the capacity is also limited. Fig.16 It can be seen that the comparative example 1 without adding zinc source has a -1 The capacity after 1000 cycles is only 73.4 mAh g -1, and Example 4 when the ratio of ammonium metavanadate to zinc sulfate heptahydrate is 8:1 at 5Ag -1 The capacity after 1000 cycles can reach 188.3 mAh g -1 Compared with the comparative example 1 without adding zinc source, the capacity is greatly improved. Fig.10 As shown in Table 1, Example 6, Example 4 and Example 7 have a -1 The capacity after 1000 cycles is 76.2 mAh g -1 、188.3mAh g -1 and 120.3mAh g -1 , indicating that the calcination temperature has a great influence on the battery performance, and the performance is best when the temperature is 400℃. Fig.14 As shown in Table 1, in Example 8, Example 4 and Example 9, the -1 The capacity after 1000 cycles is 84.3 mAh g -1 、188.3mAh g -1 and 143.5mAh g -1 , indicating that the performance is best when the reaction time is 4h.
[0093] The above embodiments are preferred implementations of the present invention, but the implementations of the present invention are not limited to the above embodiments. The technical features of the above embodiments can be arbitrarily changed, combined, replaced, modified, and simplified, but should be regarded as equivalent replacement methods and should be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material for an aqueous zinc ion battery, characterized in that: The following steps are involved: S1. Mix and grind ammonium metavanadate and zinc sulfate or its hydrate to obtain a reaction precursor; S2. calcining the reaction precursor obtained in S1 under a protective atmosphere.
2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of ammonium metavanadate to zinc sulfate or its hydrate is (1-16):1, preferably 8:
1.
3. The preparation method according to claim 1, characterized in that: In step S2, the calcination temperature is 400-500°C, preferably 400°C.
4. The preparation method according to claim 1, characterized in that: In step S2, the calcination time is 3 h to 5 h, preferably 4 h to 5 h, and more preferably 4 h.
5. The zinc ion-doped VO2 material prepared by the method according to any one of claims 1 to 4.
6. The use of the zinc ion doped VO2 material according to claim 5, characterized in that: Used to prepare positive electrode materials for aqueous zinc ion batteries.
7. A positive electrode material for an aqueous zinc ion battery, characterized in that: Made of the zinc ion-doped VO2 material as described in claim 6.
8. A positive electrode plate for an aqueous zinc ion battery, characterized in that: Comprising the positive electrode material as claimed in claim 7.
9. An aqueous zinc ion battery, characterized in that: Including the positive electrode sheet as described in claim 8.
Citation Information
Patent Citations
Vanadium pentoxide intercalation material, preparation method thereof and application of vanadium pentoxide intercalation material in aqueous zinc ion battery
CN115417455A
Vanadium oxide with in-situ derived heterostructure as well as preparation method and application of vanadium oxide
CN115483392A